Bilateral Peritonsillar Cellulitis in a 38-Year-Old Female: A Case Report - Rian Kurniawan Laksono; Nicholas Adriel Pinzon; Aurora Putri Prameswari; Maydeline Kezia Puspa Negoro (Ilmu Bersama Center, 2026)
Peritonsillar cellulitis represents an inflammatory reaction of the tissue between the palatine tonsil capsule and pharyngeal muscles without pus collection, representing a stage in the progression from acute tonsillitis to peritonsillar abscess. Bilateral involvement is uncommon and presents diagnostic challenges as classic unilateral signs are absent. Case report: A 38-year-old female presented with five days of progressive sore throat, fever, dysphagia, and hot potato voice. Physical examination revealed bilateral peritonsillar swelling, hyperemia, and edema with T3-T3 tonsillar hypertrophy and exudate. Aspiration of both peritonsillar areas produced no pus. Laboratory studies demonstrated leukocytosis with neutrophilia. The patient was admitted and treated with intravenous third generation cephalosporin (ceftriaxone), metronidazole, glucocorticoid (methylprednisolone), and supportive care. After three days, swelling subsided, leading to discharge with plans for interval tonsillectomy. Conclusion: This case demonstrates that bilateral peritonsillar cellulitis can mimic abscess clinically but requires different management. Negative aspiration distinguishes cellulitis from abscess, guiding conservative treatment and timing of definitive surgical intervention.